PHOSPHODIESTERASE 5 INHIBITORS EFFECTS ON ADAPTATION TO HIGH ALTITUDE, HAPE PREVENTION AND TREATMENT: A LITERATURE REVIEW - Wojciech Bednarz; Katarzyna Torbacka; Katarzyna Rozkosz; Joanna Kaczor; Zuzanna Wróbel; Olga Jakubik; Natalia Wróbel; Aleksandra Sosin; Patrycja Podlejska; Maja Torbacka (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: High-altitude pulmonary edema (HAPE) is a life-threatening, non-cardiogenic form of pulmonary edema that typically occurs within 2-4 days after rapid ascent above 2,500 meters. It is characterized by hypoxia-induced pulmonary hypertension, increased capillary hydrostatic pressure, and defected alveolar-capillary barrier integrity. Current preventive strategies include gradual ascent and acclimatization, while descent and supplemental oxygen remain the mainstays of treatment. Pharmacological options, including phosphodiesterase type 5 (PDE5) inhibitors such as sildenafil and tadalafil, appear as promising agents due to their pulmonary vasodilatory effects mediated via the nitric oxide (NO)–cGMP pathway. Description of the state of knowledge: This review synthesizes findings from clinical trials, case series, and mechanistic studies published in the last three decades to evaluate the efficacy and safety of PDE5 inhibitors in both the prevention and treatment of HAPE. Evidence indicates that sildenafil and tadalafil effectively reduce pulmonary artery pressure, improve oxygenation, and preserve endothelial barrier function under hypoxic conditions. Their prophylactic use significantly lowers HAPE incidence in high-risk individuals, while therapeutic administration has demonstrated clinical improvement in established cases, particularly when nifedipine use is contraindicated. However, results from some high-altitude trials remain inconclusive, and individual responses may vary based on ascent profile and susceptibility. Conclusions: Overall, PDE5 inhibitors represent a viable adjunct in HAPE management. Further large-scale, randomized studies are necessary to clarify their optimal use, dosage, and comparative efficacy alongside existing pharmacologic options.